2007
DOI: 10.1007/s00432-007-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

CXCL5 overexpression is associated with late stage gastric cancer

Abstract: CXCL5 overexpression was associated with late stage gastric cancer and high N stage. These results suggest a role for CXCL5 in the progression of gastric cancer, specifically in lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 35 publications
(32 reference statements)
1
70
2
Order By: Relevance
“…Previous studies have shown that overexpression of CXCL5 is present in numerous human tumors including prostate, squamous cell and stomach tumors. Additionally, CXCL5 may have an important role in the occurrence and progression of tumors by cooperating with its receptor C-X-C chemokine receptor type 2 (CXCR2) (14)(15)(16). Although a previous study by Zhou et al (17) demonstrated that the expression of CXCL5 in hepatocellular carcinoma tissues was evidently increased compared with that in para-carcinoma tissues and overexpression of CXCL5 can promote the growth and invasion of hepatocellular carcinoma cells, the effects of CXCL5 contributing to the growth and migration of HB cells through the autocrine/paracrine pathways have not, to the best of our knowledge, been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that overexpression of CXCL5 is present in numerous human tumors including prostate, squamous cell and stomach tumors. Additionally, CXCL5 may have an important role in the occurrence and progression of tumors by cooperating with its receptor C-X-C chemokine receptor type 2 (CXCR2) (14)(15)(16). Although a previous study by Zhou et al (17) demonstrated that the expression of CXCL5 in hepatocellular carcinoma tissues was evidently increased compared with that in para-carcinoma tissues and overexpression of CXCL5 can promote the growth and invasion of hepatocellular carcinoma cells, the effects of CXCL5 contributing to the growth and migration of HB cells through the autocrine/paracrine pathways have not, to the best of our knowledge, been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CXCL5 expression contributes to tumor progression and metastasis (30)(31)(32). Park et al demonstrated that CXCL5 overexpression was associated with advanced gastric cancer and high N stage, suggesting a role for CXCL5 in the progression of gastric cancer, specifically in lymph node metastasis (33).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a meta-analysis carried out by Liu et al [135] indicated that the variable results reported by many different studies can be affected by differences of histological type, tumor location, H. pylori infection, ethnicity and geographic location [136] . Another CXC chemokine, CXCL5, was also reported recently to be a potential molecular marker for cancer development, especially for late stage gastric cancer [137] . However, it is not yet confirmed if this observation is a consequence of secondary change as a result of gastric cancer progression, or whether it is one of the primary molecular events leading to tumor development.…”
Section: Stomachmentioning
confidence: 97%
“…Marker for late stage gastric cancer [137] Other candidates CC-chemokines (CCL2, 3, 5, 21, 25)/CXC-chemokines (1,7,8,12,14)/CCR6 [139] Liver CXCR4 Metastasis, upregulation in PVTT [142][143] …”
Section: Cxcl5mentioning
confidence: 99%